Implementation of Protection of Spiritual Needs for Indonesian Citizens in the Class IIB Detention Home, Tanjung Pura - Arief Septiawan; T. Riza Zarzani (International Journal of Law and Society, 2024)
The spiritual and physical care of prisoners is very influential in life, starting from religious life and health. This formation means that all efforts are made to raise awareness and always maintain regularly the existence of religious and health values, with the aim that human behavior always remains within the norm. -good norms. The aim of this research is to find out the implementation of spiritual and physical care for prisoners at the Class IIB Tanjung Pura Narcotics Correctional Institution, the obstacles in implementing spiritual and physical care for prisoners at the Class IIB Tanjung Pura Detention Center and the efforts of the Class IIB Tanjung Pura Detention Center to overcome obstacles in the implementation of spiritual and physical care for prisoners. This research is included in descriptive research with the type of Normative juridical research using qualitative analysis methods. From the results of the research, the Class IIB Tanjung Pura Detention Center fulfills the rights of inmates in the form of providing spiritual care for inmates in the form of religious formation activities and the implementation of worship, while the implementation of physical care in the form of maintaining body fitness through morning exercise, sports, channeling hobbies through art. , recreation with family visits as well as support in providing proper and adequate nutrition and health care. The obstacles experienced by the Class IIB Tanjung Pura Detention Center in fulfilling the right to spiritual and physical care include the limited budget of the Class IIB Tanjung Pura Detention Center, human resources in terms of quality and quantity, and the facilities at the Class IIB Tanjung Pura Detention Center are inadequate. The efforts of the Class IIB Tanjung Pura Detention Center to overcome obstacles in implementing spiritual and physical care for prisoners include maximizing the use of the budget of the Class IIB Tanjung Pura Detention Center, providing training and using the services of lecturers, maximizing the facilities of the Class IIB Tanjung Pura Detention Center.